The societal burden of chronic liver diseases: results from the COME study. Issue 1 (31st December 2015) - Scalone, Luciana; Fagiuoli, Stefano; Ciampichini, Roberta; Gardini, Ivan; Bruno, Raffaele; Pasulo, Luisa; Lucà, Maria Grazia; Fusco, Francesco; Gaeta, Laura; Del Prete, Anna; Cesana, Giancarlo; Mantovani, Lorenzo Giovanni
Abstract : Objective: Chronic liver diseases (CLDs) impose a significant socioeconomic burden on patients and the healthcare system, but to what extent remains underexplored. We estimated costs and health-related-quality-of-life (HRQoL) among patients with CLDs at different stages and with different aetiologies. Design: A cost-of-illness study was conducted. Direct costs, productivity loss and HRQoL were estimated in patients with chronic hepatitis, cirrhosis hepatocellular carcinoma (HCC) or where orthotopic liver transplantation (OLT) had been performed, for hepatitis C virus (HCV) infection, hepatitis B virus (HBV) infection, or in those with liver disease from other causes. Patients were retrospectively observed for 6 months. The societal perspective was adopted to calculate costs. Results: In total, 1088 valid patients (median age=59.5 years, 60% men) were enrolled. 61% had chronic hepatitis, 20% cirrhosis, 8% HCC and 12% underwent OLT. HCV infection was identified in 52% and HBV infection in 29% of the patients. Adjusted mean direct costs increased from <€200/patient-month in HCV-infected patients with hepatitis to >€3000/patient-month in HBV infected patients with OLT. Antiviral treatment was the cost driver in patients with hepatitis, while hospital costs were the driver in the other subgroups. Absenteeism increased from HBV-infected patients with hepatitis (0.7 day/patient-month) to patients with OLT with other aetiologies (3.7 days/patient-month). HRQoL was on average more compromised in cirrhosis and patients with HCC, than in hepatitis and patients with OLT. HBV-infected patients generated higher direct costs, patients with other aetiologies generated the highest productivity loss and HCV-infected patients reported the worst HRQoL levels. Conclusions: The present study can be considered a benchmark for future research and to guide policies aimed at maximising the cost-effective of the interventions.